Assessment of autonomic nervous function in patients with vibration syndrome using heart rate variation and plasma cyclic nucleotides. Issue 4 (April 1990) - Harada, N; Kondo, H; Kimura, K
Abstract : A case-control study was performed to investigate the autonomic nervous function in vibration syndrome. The subjects were 20 patients with a history of Raynaud's phenomenon (vibration white finger (VWF) (+) group), 20 patients without such a history (VWF(-) group), and 20 healthy workers (control group). Their ages and years under medical treatment for vibration syndrome were matched individually among the groups. They were examined using the test of R-R interval variations in the electrocardiogram at rest and during deep breathing and the test of plasma cyclic nucleotide (cyclic AMP and cyclic GMP) responses to whole body exposure to cold. The heart rate variation resulting from respiratory arrhythmia reflects parasympathetic activity; the changes of plasma cyclic AMP and GMP levels reflect sympathetic and parasympathetic receptor functions. The reduced R-R interval variations were observed in the VWF(+) group. Although exposure to cold induced a significant increase of plasma cyclic AMP level, the percentage increase was almost the same among the three groups. The response of plasma cyclic GMP level to cold exposure was highly activated in the VWF(+) and the VWF(-) groups. On the basis of these results, it is considered that the parasympathetic function of patients with vibration syndrome is lower at rest, and that exposure to cold induces a hypperresponse of the parasympathetic nervous system and the alpha-2 adrenergic mechanism as a result of activation of the sympathetic nervous system. Moreover, in patients with VWF, the contribution of the alpha-2 adrenergic mechanism is presumably larger than that in the patients without VWF.